Analysis of Different Impression Techniques and Materials on Multiple Implants Through 3-Dimensional Laser Scanner. Issue 2 (April 2016) - Pera, Francesco; Pesce, Paolo; Bevilacqua, Marco; Setti, Paolo; Menini, Maria
Abstract : Objective: The aim of this study was to evaluate the accuracy of 7 different implant impression techniques for full-arch prostheses. Materials and Methods: A master cast simulating an edentulous arch with 4 implants was used. Seven impression techniques were tested: open tray with polyether Impregum (OTI); open tray with splint-polyether Impregum (OTSI); closed tray with polyether Impregum; open tray with polyether Ramitec; open tray with splint-polyether Ramitec; closed tray with polyether Ramitec (CTR); open tray with impression plaster (OTP). Five impressions of the master cast were taken for each technique using an impression simulator device. Casts were realized based on those impressions (n = 35). Median values of deviation from the master cast were recorded for each cast through a 3-dimensional laser scanner. Results: Only OTI ( P = 0.028) and OTSI ( P < 0.001) presented a statistically significant difference compared to the master cast. OTP ( P = 0.99) and CTR ( P = 0.10) showed median values of deviation close to zero (−0.001 and −0.003 mm, respectively). Conclusion: Stiff impression materials (such as plaster or rigid polyether) guarantee greater accuracy in cases of multiple implant impressions of patients with full-arch rehabilitations. Splinting of impression copings with acrylic resin did not improve accuracy.